Effects of Polymer Coating Mechanics at Solid‐Electrolyte Interphase for Stabilizing Lithium Metal Anodes. Issue 5 (22nd December 2021) - Huang, Zhuojun; Choudhury, Snehashis; Paul, Neelima; Thienenkamp, Johannes Helmut; Lennartz, Peter; Gong, Huaxin; Müller‐Buschbaum, Peter; Brunklaus, Gunther; Gilles, Ralph; Bao, Zhenan
Abstract: Lithium metal batteries are next‐generation energy storage devices that rely on the stable electrodeposition of lithium metal during the charging process. The major challenge associated with this battery chemistry is related to the uneven deposition that leads to dendritic growth and poor coulombic efficiency (CE). A promising strategy for addressing this challenge is utilizing a polymer coating on the anodic surface. While several works in the past have evaluated polymer coatings, the requirements for polymer design are still unclear. In this work, the effect of polymer dynamics on lithium metal deposition is specifically investigated. Electrolyte (solvent) blocking perfluoropolyether polymer networks with evenly spaced H‐bonding sites of various strengths are designed, resulting in significant differences in the molecular ordering, as analyzed by X‐ray scattering measurements. The differences in the H‐bonding strength directly impact the mechanical properties of these materials, thus providing a controlled set of samples with a range of polymer dynamics for electrodeposition studies. Finally, a systematic evaluation of the lithium metal electrodeposition quality with these polymers as anodic coating shows that polymers with flowability or faster polymer dynamics exhibit higher CE. These experimental findings provide rational design principles for soft polymer coatings on lithium metal anodes. Abstract : In this work, PFPE‐based polymer networks are systematically varied with evenly spaced H‐bonding sites of different bonding strengths. It is found that the viscous and viscoelastic polymer coatings maintain homogenous coverage during cycling and result in higher coulombic efficiencies. This work suggests that mechanical properties of the polymer coating on lithium metal is an important parameter for consideration.